Elementos da administração estratégica no auxílio da teologia pastoral - Pereira, Pedro Luiz Amorim (2020)
This academic work, at master's level, has as main objective to point out some elements of Strategic Administration that can be applied in Pastoral Theology, especially with regard to the “acting” of the see-judge-act method created by Jospeh Cardjin. The bases for the dialogue between these two sciences were built through the study of Synodality in the Church since the Sacred Scriptures, passing through the continuities and discontinuities of this way of ecclesial participation throughout history, and exemplifying its applicability in closer contexts such as the Episcopal Council Latin American (CELAM), the National Conference of Bishops of Brazil (CNBB) and the Archdiocese of São Paulo itself, which recently promoted its first Archdiocesan Synod. Although the calling of an Archdiocesan Synod is a bold attitude, the composition and paths of the synod indicate an ecclesiology that is not open to the effective participation of the laity, emphasizing a clerical character that prevents a greater role of the laity in the instances of discernment of the laity itself in ecclesial paths of the Archdiocese of São Paulo. The analysis of this scenario comes from the study of some results of the field research carried out by the Archdiocese of São Paulo during the preparatory phase of the Synod. From the formulation of the research questionnaire to its graphic presentation, it is possible to see that the ecclesiological model needs to be revised in many areas, as it leaves aside an opportunity for true listening and contribution from an important part of the Church that does not seem to find a place from which they can express their perceptions and opinions. Despite being extremely competitive and individualizing, the business environment works with the view that the people who make up an organization are a fundamental part in any business strategy. Based on this principle, the present work seeks to establish a dialogue between Pastoral Theology (which seeks to order the evangelization job) with Strategic Administration (which seeks to establish some principles for an organization to achieve its objectives). It is not a matter of pointing out immediate pastoral solutions, but, starting from some organizational and ecclesiological principles, perceiving some important gaps that can be fundamental points in the construction of an effective pastoral organization